(3CfHGA GdGUWaG aj Mb BHGA GdoeUWais - (3eMeO Hf bGSe Hf jYbhH GdCeGSj , eMjj GdOjf, GdTgjQ HGHf GdNWjHs; (3GdGeGSj , eMeO Hf bGSe Hf jYbhH GdMfaj Hf GdNWjH bGSe, eMjj GdOjf,J (B940 (3g` s ((3jhSa Hf YHOGddg Hf eMeO GdOjQjfj GdTGaYj s)
(3ChdgG (B:s
(3CeG HYO agPg QSGdI UOQJ Yf GdUOQ GdSGei, GdZQjb ai GdedGgj ai TQa BHGA UOQ GdQSGdI , hWgGQJge Yf GdNjGfI hGdQPGdI s
(3BNQgG (B:s
(3hQMe CSdGag GdeGVjf ef GdZRGI hGdSdGWjf aj cQSj HdGO GdGSdGe HeOQSI CjGUhajI ai HdOI bSWfWjfjI MeGgG Gddg JYGdi HaVdg hcQeg Yf fcHGJ GdCjGe s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B148s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B51 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs